Q-RUSH Hysterectomy: A Mini Review of a Novel, Rapid, and Vault-Supportive Modification of Traditional Total Abdominal Hysterectomy - Nawaz, Qudsia; Ghaffar, Sadia A.; Khawar, Maliha; Naqvi, Siddiqa Batool; Shakeel, Shazia; Tanvir, Neha; Tanvir, Ayesha; Tabassum, Humaira (Biological and Clinical Sciences Research Journal, 2025)
Background: Total abdominal hysterectomy often requires multiple sequential pedicle clamps and separate vault suspension steps, which can prolong operative time, increase surgeon fatigue, and result in variable apical support. Optimizing both operative efficiency and post-hysterectomy vault support remains a key surgical priority. Objective: To describe the conceptual basis, surgical rationale, and potential advantages of Qudsia’s Rapid Unified Suspension Hysterectomy (Q-RUSH) technique as an innovative modification of total abdominal hysterectomy. Methods: This mini-review synthesizes the development and operative concept of Q-RUSH, which streamlines pedicle management and incorporates uterosacral–transcervical ligament suspension into a single, continuous suture technique. Relevant literature on total abdominal hysterectomy, apical suspension, and prevention of post-hysterectomy vault prolapse was narratively reviewed to contextualize Q-RUSH within current practice. Early pilot experience from its use in a tertiary care setting was examined descriptively with respect to operative workflow, hemostatic control, and urinary tract safety; no formal hypothesis testing or comparative statistical analysis was undertaken. Results: Q-RUSH conceptually reduces the number of separate pedicle clamps and consolidates apical support into an integrated suspension step, which appears to shorten operative workflow and lessen intraoperative handling. Early pilot observations indicate meaningful time savings with maintained hemostasis and no evident compromise in urinary tract safety. By providing immediate, anatomically anchored apical support via a continuous uterosacral–transcervical suspension, Q-RUSH may help reduce the risk of post-hysterectomy vault prolapse. However, this requires confirmation in prospective comparative studies with long-term follow-up. Conclusion: Q-RUSH represents a promising modification of total abdominal hysterectomy that unifies pedicle control and apical suspension in a single continuous technique, with the potential to improve operative efficiency and apical support. Robust prospective trials with adequate sample size, standardized outcome measures, and long-term follow-up are needed to validate its safety profile and efficacy in preventing post-hysterectomy vault prolapse.